Intrathecal analgesia in cancer pain through local anesthetics and opioids via epidural catheter sets - Pekel, Ali Ferit (Cerrahpaşa Medical Journal, 2019)
Cancer patients who have failed to obtain adequate pain relief or develop intolerable side effects to systemically administered drugs, may benefit from intrathecal opioids combined with local anesthetics. A variety of techniques and devices have been proposed in order to perform intrathecal drug delivery. Amongst all, epidural catheter sets can be a practical, simple and cheaper tool to achieve this goal. This study shows our results, of 14 cases of cancer patients with intractable pain at progressive stages managed with intrathecal morphine/bupivacain combination delivered through epidural catheter sets.